The disruption of prenylation leads to pleiotropic rearrangements in cellular behavior in Staphylococcus aureus. Issue 5 (16th January 2015) - Krute, Christina N.; Carroll, Ronan K.; Rivera, Frances E.; Weiss, Andy; Young, Ryan M.; Shilling, Andrew; Botlani, Mohsen; Varma, Sameer; Baker, Bill J.; Shaw, Lindsey N.
Summary Prenylation is the addition of prenyl groups to peptide chains or metabolites via the condensation of geranyl‐ or isopentenyl‐diphosphate moieties by geranyltranstransferases. Although this process is extensively studied in eukaryotes, little is known about the influence of prenylation in prokaryotic species. To explore the role of this modification in bacteria, we generated a mutation in the geranyltranstransferase (IspA) of Staphylococcus aureus. Quite strikingly, the ispA mutant completely lacked pigment and exhibited a previously undescribed small colony variant‐like phenotype. Further pleiotropic defects in cellular behavior were noted, including impaired growth, decreased ATP production, increased sensitivity to oxidative stress, increased resistance to aminoglycosides and cationic antimicrobial peptides, and decreased resistance to cell wall‐targeting antibiotics. These latter effects appear to result from differences in envelope composition as ispA mutants have highly diffuse cell walls (particularly at the septum), marked alterations in fatty acid composition and increased membrane fluidity. Taken together, these data present an important characterization of prokaryotic prenylation and demonstrate that this process is central to a wealth of pathways involved in mediating cellular homeostasis in S. aureus.